ANALISIS KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA KEDAI ROMO KOPI KEDIRI) - Alfinasari, Safitri; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to analyze and examine the relationship (correlation) between product quality variables, service quality variables and customer satisfaction variables at Kedai Romo Kopi Kediri as the object of research. Kedai Romo Kopi is a coffee shop with its address at Jalan Harinjing 128, Kepung Barat, Kediri. The research method used in this research is descriptive quantitative with a sample of 35 people of various ages and genders. The research hypotheses were tested using multiple linear regression using the SPSS application. The results of data analysis show the conclusion that the product quality variable as X1 and service quality as X2 has a significant effect on the variable (Y) of consumer satisfaction partially (separately) or jointly (simultaneously).